Academic writing the effectiveness of library reference service in Tun Dr. Ismail Library, UiTM Johor / Nor Sabariah Al-Rahim - Al-Rahim, Nor Sabariah (2014)
The research purposed is to study about the effectiveness of library reference service in Perpustakaan Tun Dr. Ismail, UiTM Johor. This research cover about the medium that student mostly used and whether in-person or virtual library reference service. This research also finds out about his frequent question asked by the user in reference service. The user's perception of the librarian and library staff also has been discussed in this study in chapter four and five. This research will also cover about user's satisfaction toward library reference service. At the end of the research, it also has come out with the discussion abut the data and finding. Relevant recommendation also being provide to support this research.